Analisis Hazard Identification, Risk Assessment, and Risk Control (HIRARC) di Bagian Finishing 2 Industri Serikat Pekerja Aluminium Sorosutan Tahun 2017 - Dewi KuSumawardhani; Heru Subaris Kasjono; Purwanto Purwanto (Sanitasi: Jurnal Kesehatan Lingkungan)
The progress in industrial sector faces many problems that is important to be studied because hazard may lead to risks that affect health problem or even work accidents. An industry needs Occupational Health Safety (OHS) system with Hazard Identification, Risk Assessment, and Risk Control (HIRARC) method, that it is applied, dangerous activities can be easy to be found and controlled immediately, according to the magnitude of the risk level (urgent, high, medium, and low). The study was conducted in Industri Serikat Pekerja Aluminium Sorosutan and the purpose was to know the description of hazard identification, risk assessment, and risk control especially in finishing section 2. The study results show that the percentage of potential hazard categorized as urgent is 5 % in the lathing room and 6 % in welding room. Meanwhile, the per-centage of potential hazard which is categorized as high is 22 % in polishing room, 38 % in broming room, 36 % in grinding room, 33 % in quality control room, and 20 % in product clean-ing room. Based on the result, it can be concluded that the highest hazard which is categorized as urgent is exist in two production rooms; i.e. lathing and welding rooms; and the production rooms that belong to high category are polishing room, broming room, grinding room, quality control room, and produc cleaning room.